Permainan Tradisional Egrang Untuk Meningkatkan Keterampilan Sosial Dan Kecerdasan Kinestetik Anak SD - Afakhrul Masub Bakhtiar; Arya Setya Nugroho (Universitas Negeri Surabaya, 2017)
Civilizing traditional game local wisdom through the younger generation, and patenting intellectual property is the long-term goal that the researcher wants to realize. Traditional games which are one of the nation's intellectual property, contain very conditions for the meaning of life. In specific targets, researchers want to improve the social skills and kinesthetic intelligence of elementary school children through traditional